2010
DOI: 10.1093/protein/gzq105
|View full text |Cite
|
Sign up to set email alerts
|

A novel sequence-based antigenic distance measure for H1N1, with application to vaccine effectiveness and the selection of vaccine strains

Abstract: H1N1 influenza causes substantial seasonal illness and was the subtype of the 2009 influenza pandemic. Precise measures of antigenic distance between the vaccine and circulating virus strains help researchers design influenza vaccines with high vaccine effectiveness. We here introduce a sequence-based method to predict vaccine effectiveness in humans. Historical epidemiological data show that this sequence-based method is as predictive of vaccine effectiveness as hemagglutination inhibition assay data from fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 30 publications
1
74
0
Order By: Relevance
“…These two fitted models predict a vaccine effectiveness of 47% when p epitope  = 0 for A/H3N2 and of 53% when p epitope  = 0 for A/H1N1 [21], [23].…”
Section: Methodsmentioning
confidence: 99%
“…These two fitted models predict a vaccine effectiveness of 47% when p epitope  = 0 for A/H3N2 and of 53% when p epitope  = 0 for A/H1N1 [21], [23].…”
Section: Methodsmentioning
confidence: 99%
“…We selected these antigenic distance values to reflect ∼100% cross-reactivity of Abs to the conserved face epitope and ∼20% cross-reactivity of Abs to the polymorphic face epitope suggested in the monovalent vaccination results (47). In cases in which experimental data from a vaccination study are unavailable, the antigenic distance can be inferred from in vitro testing of serum samples (31) or estimated from epitope sequence identity (64,65). A third epitope-specific parameter, neutralization (r 1 and r 2 ), was set to 1.0 for both epitopes to reflect experimental data, which suggested that both epitopes have comparable neutralization characteristics (47).…”
Section: Overall Immune System Modelmentioning
confidence: 99%
“…Much of the evolution of influenza in both species involved substitutions of charged or hydrophobic amino acid residues or mutations that led to changes in glycosylation profile [18]. Influenza virus undergoing escape evolution in Guinea pigs also showed a tendency to substitute the amino acids in the epitope regions, which was also observed in human influenza [6], [27]. Consequently, the evolution of the virus in Guinea pigs represents a valuable model system for helping us to understand the escape evolution of human influenza virus.…”
Section: Discussionmentioning
confidence: 93%